Evaluation of academic level of scientific literacy of freshmen and seniors of graduate courses (Research, Society and Development, 2020)
We present the results of a quantitative research that aimed to infer and compare the level of Scientific Literacy of 194 1undergraduate and senior students in undergraduate courses at a University in the interior of Rio Grande do Sul, Brazil. The justification for the study involves the desire to know the impact of academic experience on the scientific education of future teachers who are in the process of initial training. For this, a reduced version of the Test of Basic Scientific Literacy (TBSL) was used. Specifically, this research sought to infer the understanding of undergraduates in the three dimensions of Scientific Literacy postulated by the theoretical framework: understanding the contents of science, the nature of science and the impact of science on society and the environment. As results, it was observed that there are differences in the average of correct answers between entering and concluding courses studied. However, these differences could not be considered statistically significant. These findings are in line with the results described by the literature when investigating chemistry and biology courses from this perspective. It is recommended that other studies be conducted replicating the methodology used, in order to provide support to compare the data and conclusions obtained from the different courses of initial teacher training.